Proceedings of the 2018 International Conference on Big Data Engineering and Technology 2018
DOI: 10.1145/3297730.3297743
|View full text |Cite
|
Sign up to set email alerts
|

Big Data Platform Architecture under The Background of Financial Technology

Abstract: With the rise of the concept of financial technology, financial and technology gradually in-depth integration, scientific and technological means to become financial product innovation, improve financial efficiency and reduce financial transaction costs an important driving force. In this context, the new technology platform is from the business philosophy, business model, technical means, sales, internal management and other dimensions to re-shape the financial industry. In this paper, the existing big data p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…The bottom-up approach method occurs in two steps, namely Schema Translation and Schema Generation which both help the process of converting each data source schema into a common representation to make it easier to analyze and process (Rachman et al, 2017). Using a big data platform combined with space-time data could integrate its own data resources and provide cost reduction, followed by risk prevention which is pretty much helpful for business (Liu et al, 2018). This could also be an option.…”
Section: Analysis Of Real Actionsmentioning
confidence: 99%
“…The bottom-up approach method occurs in two steps, namely Schema Translation and Schema Generation which both help the process of converting each data source schema into a common representation to make it easier to analyze and process (Rachman et al, 2017). Using a big data platform combined with space-time data could integrate its own data resources and provide cost reduction, followed by risk prevention which is pretty much helpful for business (Liu et al, 2018). This could also be an option.…”
Section: Analysis Of Real Actionsmentioning
confidence: 99%
“…Thus reducing organizational citizenship behavior. Besides, [24] also explored the relationship between perceived responsibility, psychological privilege, and job satisfaction based on the resource conservation theory. The study found that in situations with low levels of accountability, psychologically privileged workers spend many resources on cognitive filtering and maintaining a positive self-image, and the loss of resources will make them feel more stressed, thus reducing job satisfaction.…”
Section: Psychological Senses Of Privilege From the Perspective Of Rementioning
confidence: 99%
“…Because of the RCEP's substantial results in 2019, this article uses China, Japan, and South Korea as an example to explore the path of expanding trade between China and Japan and South Korea. At the same time, drawing on the experience of developed countries, the article argues that China should also establish free trade zones with significant world economies, which is of considerable significance to China's right to speak in the trading system [2][3].…”
Section: Introductionmentioning
confidence: 99%